KESIAPAN KAMPUS UNTUK KEGIATAN PERKULIAHAN YANG BERADAPTASI DALAM ERA NEW NORMAL: Studi Kasus: Ruang Studio Jurusan Arsitektur di Gedung Agape, Universitas Kristen Duta Wacana, Yogyakarta - Edward S. Sudharsono; Paulus Bawole (ATRIUM: Jurnal Arsitektur, 2020)
Title: Campus Readiness Toward Lecture Activities in the New Normal Era The Covid-19 pandemic, which has been going on for so long, is not yet known when it will end. Under these conditions, all activities that involve large numbers of people need to seek prevention against the risk of disease transmission. Lecture activities that are usually carried out face-to-face (offline) are currently conducted online. However, at certain times the lecture activities must be done offline. At the Department of Architecture – Duta Wacana Christain University (UKDW), some of the offline lecture activities are carried out in the studio room. Although not every day, this activity still has a chance for disease transmission. For this reason, offline lectures at UKDW need to be reviewed so that all activities that take place on campus can prevent disease transmission as much as possible. Regulation of the Minister of Health regarding health protocols and other related regulations are used to identify the readiness of lecture rooms, especially studio rooms in which the lecture activities in the Architecture Department - UKDW are carried out. The problem that happens is the risk of transmission due to the level of readiness of the studio room and the layout of the furniture in fulfilling the standard health protocol. This study applies a descriptive - qualitative method with data taken from observation and interviews. The results of the examination of the studio rooms show that the studio rooms still need to be adapted to standard health protocols and other applicable regulations.